Longevity of Cane Corso Italiano dog breed and its relationship with hair colour - Korec, Evžen; Chalupa, Ondřej; Hančl, Matyáš; Korcová, Jana; Bydžovská, Marie (Open veterinary journal, 2017)
The Cane Corso Italiano belongs among the new dog breeds that were fully recognised by Federation Cynologique Internationale (FCI) in 2007. For the first time, this study describes a median lifespan using the data of 232 dogs of the Cane Corso Italiano breed collected from kennels and individual owners from 25 countries. The median lifespan of the whole examined group is 9.29 years (IQR 6.98-11.12, IQR = Interquartile Range). This paper is the first to describe the possible relationship between median lifespan and hair colour within one breed. The longest living group is formed by black brindle coloured dogs, with a median of 10.30 years (IQR 8.33-13.00), and brindle coloured dogs, with a median of 10.13 years (IQR 7.12-11.25). The median lifespan of black brindle dogs exceeded the overall median lifespan of all dogs by 1.01 year and the median lifespan of other colour dogs by 2.21 years. Our results suggest a possible way for a prolongation of age at death of the Cane Corso Italiano breed using appropriate breeding. The median lifespan of male Cane Corso Italiano dogs is 9.25 years (IQR 6.97-11.00) and female Cane Corso Italiano dogs 9.33 years (IQR 7.00-11.31). The statistical analysis using the Independent Samples Student's t test confirmed that the lifespan of female dogs did not exceed the median lifespan of male dogs (P>0.01).
Keywords: Life Prolongation; Kennel; Cane Corso Italiano; Lifespan; Dog Breed